Outcomes of participating in the Let’s Play programme on 0–5-year-old autistic children’s engagement and caregivers’ stress: study protocol for a parallel randomised controlled trial - Philip J Schluter; Laurie McLay; Jenna van Deurs; Lauren van Noorden; Ashley E Hinten (BMJ Open)
Introduction Vast empirical evidence highlights the importance of early identification, diagnosis and support for autistic children. Caregivers of autistic children often experience high levels of psychological distress; hence there is a need for parallel child and caregiver support. Autism New Zealand’s Let’s Play programme is a caregiver-mediated, community-based programme based on the principles of developmental and relational interventions (henceforth, developmental). Developmental interventions are evidence-based supports designed to enhance children’s learning within the context of developmentally appropriate, naturalistic settings (eg, everyday routines, play). We aim to evaluate the effects of the Let’s Play programme on autistic children’s engagement and caregiver stress.Methods and analysis This study will be a single-blind (rater) randomised controlled trial with two parallel arms: immediate programme access (intervention) versus a waitlist control. Participants will be 64 caregivers of children aged 0–5 years with diagnosed or suspected autism, allowing for 20% attrition, based on power calculations. The Let’s Play programme will be delivered over 9 weeks using a combination of small group workshops and in-home coaching. Primary outcome variables include child engagement and caregiver stress. Caregivers will complete measures at three time points (baseline, immediately post-programme and at the 6-month follow-up), and effectiveness will be analysed using generalised estimating equation models and intention-to-treat and per protocol analyses.Ethics and dissemination This trial was approved by Aotearoa New Zealand Ministry of Health’s Health and Disability Ethics Committee (2022 FULL 13041). Findings will be communicated nationally and internationally via conferences, journal publications and stakeholder groups (eg, service providers for autistic children). Results will be shared regardless of magnitude or direction of effect.Trial registration number ACTRN12622001139763.